Lucretius - Schindler, Claudia, author.
1 online resource
Keywords: Lucretius’ De rerum natura , written around 55 BCE, ranks among the most influential texts in Roman literature. The poet’s vision of a world made of atoms, his mockery of the fear of death and the gods, and fervent advocacy of the mortality of the soul over many centuries incensed his critics on one hand, and on the other earned him a devoted following. This volume provides an introduction to the oldest completely preserved Latin didactic poem and to the most important research questions concerned with the text.